Support in Preparing Macroeconomic Papers - Nabila Qistina; Zara Amal Nayla (International Journal of Social Science and Humanity, 2024)
Preparing macroeconomic texts requires comprehensive support to produce quality work. This study aims to identify and analyze various forms of support needed in the process of preparing macroeconomic texts. A deep understanding of macroeconomic concepts is an important basis. Support in the form of training and access to the latest literature is needed to increase the author's understanding of current macroeconomic issues. Mastery of technology and statistical software is crucial in analyzing economic data. Support in the form of information technology training can increase the efficiency of writers in using these tools.